Behager Fikir Guzo - Abiyu Berlie (Yekatit Paper Converting PLC; Addis Ababa, 2011)
fascinating autobiography by Abiyu Berlie. The author was born in 1950 in a little rural village, named Gish Abay, in Gojjam province of Ethiopia. He went to school and eventually managed to get into Haile Sellassie I University in Addis Ababa (at the time, the only one in the country). He was then immediately caught in a wave; in the midst of a stormy student movement of the 60s; and he withdrew from 3rd year (while an honor student) to join the struggle for freedom, justice & democracy. The book tells an amazing story of a long journey; full of ups and downs, which he managed to pass through with great courage, sacrifice and perseverance; all due to his great love for his people and country. He faced all that while he was just in his late teenage years and early 20's. All in all, the book is full of reflections on the realities inside Ethiopia and Somalia, in the late 60's and early 70's; and the bitter struggle between Ethiopia and Eritrea during those years. It contains many stories untold before!